IMPLEMENTASI NETWORK MANAGEMENT SYSTEM ( NMS ) MENGGUNAKAN PANDORA FMS DI PT. SAMUDRA MARINE INDONESIA - Desmira Desmira (Jurnal Khatulistiwa Informatika, 2020)
PT. Samudra Marine Indonesia (SMI) has a network where all users are connected to one computer, and a computer (server) with a network concept like this can affect the performance of RAM, processors and hard drives, due to frequent occurrence of computers on computer users always slow and the hard disk capacity is starting to full sometimes there are also computers that suddenly disconnect from the network. However, the IT technician does not know what is happening to the user's computer because the IT technician room is very far away from the SMI 2 building due to different buildings.So we need a system with the concept of Network Management System (NMS) which functions as a supervisor for the state of the server computer or client computer so that it can be handled quickly. The Network Manage-ment system (NMS) network uses the Linux Centos operating system which will be installed using the Pandora FMS application. Methods: 1. Study 1: conducting experiments (designing) .2. Study 2: analysis and design of Network Management System.The results show that the Pandora FMS application runs in accordance with the research objectives, the us-er to the server can access the Pandora FMS software. Hard disk, RAM and Processor have been efficient in monitoring performance at PT. Samudra Marine Indonesia.